2019
DOI: 10.1002/jae.2712
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in heterogeneous panels with endogenous regressors

Abstract: Summary This paper extends Pesaran's (Econometrica, 2006, 74, 967–1012) common correlated effects (CCE) by allowing for endogenous regressors in large heterogeneous panels with unknown common structural changes in slopes and error factor structure. Since endogenous regressors and structural breaks are often encountered in empirical studies with large panels, this extension makes Pesaran's CCE approach empirically more appealing. In addition to allowing for slope heterogeneity and cross‐sectional dependence, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Further, it can be used regardless whether T is greater than N or not. Baltagi et al (2018) show that Pesaran's (2006) procedure is still valid to consider crosssectional dependence stemming from error factors even in the presence of endogeneity and structural changes in slopes and error factor loadings. There are two versions of the CCE estimator for the mean value of individual coefficients,…”
Section: Estimation and Discussion Of Resultsmentioning
confidence: 92%
“…Further, it can be used regardless whether T is greater than N or not. Baltagi et al (2018) show that Pesaran's (2006) procedure is still valid to consider crosssectional dependence stemming from error factors even in the presence of endogeneity and structural changes in slopes and error factor loadings. There are two versions of the CCE estimator for the mean value of individual coefficients,…”
Section: Estimation and Discussion Of Resultsmentioning
confidence: 92%
“…( 2019 ) demonstrate that the common factor approach helps control for UCFs even under the presence of endogenous regressors. Furthermore, the cross‐sectional mean of parameters can be consistently estimated by the mean‐group type estimators with endogenous variables (MG‐IV) (Baltagi et al., 2019 ; Feng, 2020 ). 10 Accordingly, the estimated coefficient on LE is imprecisely estimated at conventional levels of statistical significance when I account for UCFs and parameter heterogeneity.…”
Section: Robustnessmentioning
confidence: 96%
“…Baltagi et al. ( 2019 ) demonstrate that the common factor approach helps control for UCFs even under the presence of endogenous regressors. Furthermore, the cross‐sectional mean of parameters can be consistently estimated by the mean‐group type estimators with endogenous variables (MG‐IV) (Baltagi et al., 2019 ; Feng, 2020 ).…”
Section: Robustnessmentioning
confidence: 99%
“…This technique uses cross-sectional demeaned variables and provides robust findings in the existence of cross-sectional dependence and heterogeneity problems. Furthermore, Baltagi et al (2019) showed that the CCE estimators are valid even in the presence of endogeneity and structural changes. After examining the long-run relationship, to determine the direction of causality between export and labour productivity, the heterogeneous panel causality test developed by Dumitrescu and Hurlin (2012) was employed.…”
Section: Econometric Approachmentioning
confidence: 99%